Fake health news in the new regime of truth and (mis)information (RECIIS, 2020)
The phenomenon of fake news in public health worldwide reflects significant changes in the regime of health information, particularly in the West. It reveals a transition from a scenario in which the medical community arguably dominated the flow of health information — grounded in the biomedical model — to a more crowded, competitive and chaotic scenario. The digital revolution has upended the old regime by transforming the large-scale production, distribution and consumption of health information. Consequently, misinformation and disinformation have become widespread, as the public is able to obtain information about health issues from an array of sources and platforms, and rogue actors flood the internet with factually incorrect information, hearsay and conspiracy theories.